2013
DOI: 10.1039/c2pp25393c
|View full text |Cite
|
Sign up to set email alerts
|

Core—shell poly-methylmethacrylate nanoparticles as effective carriers of electrostatically loaded anionic porphyrin

Abstract: Among the medical applications of nanoparticles, their usage as photosensitizer (PS) carriers for photodynamic therapy (PDT) has attracted increasing attention. In the present study we explored the morphological and photophysical properties of core-shell PMMA nanoparticles (PMMA-NPs) electrostatically post-loaded with the synthetic, water soluble 5,10,15,20-tetrakis(4-sulphonatophenyl)-porphyrin (TPPS4). pH response and singlet oxygen analyses of differently loaded samples proved the high capability of the PMM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
24
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(25 citation statements)
references
References 50 publications
1
24
0
Order By: Relevance
“…Their singlet oxygen efficacy, however, can be affected by environmental factors such as solvent, temperature, moiety attachments and the presence and proximity of quenching groups. Metal-free, water-soluble and highly stable porphyrins such as meso-tetra-(4-sulfonatophenyl) porphyrin (TPPS 4 ) have been studied for their singlet oxygen quantum yield (SOQY), tumor tissue affinity, retention times and water solubility 810. Clinical studies on TPPS 4 have shown its potential as a PDT photosensitizer; however, its biological progression has been hampered by the atypical reliance of its photo-physical properties on environmental factors as listed above.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Their singlet oxygen efficacy, however, can be affected by environmental factors such as solvent, temperature, moiety attachments and the presence and proximity of quenching groups. Metal-free, water-soluble and highly stable porphyrins such as meso-tetra-(4-sulfonatophenyl) porphyrin (TPPS 4 ) have been studied for their singlet oxygen quantum yield (SOQY), tumor tissue affinity, retention times and water solubility 810. Clinical studies on TPPS 4 have shown its potential as a PDT photosensitizer; however, its biological progression has been hampered by the atypical reliance of its photo-physical properties on environmental factors as listed above.…”
Section: Introductionmentioning
confidence: 99%
“…In addressing these inherent shortcomings of TPPS 4 and porphyrins at large, much research has focused on conjugated systems for their biological applications 8,9,11. Moreover, conjugation of TPPS 4 has shown to improve the QY of QDs and disaggregation of aged QDs which allows for a wider application range of TPPS 4 –nanomaterial conjugates 9.…”
Section: Introductionmentioning
confidence: 99%
“…[27][28][29] For example, hyperbranched polyglycerol (hPG) and oligoesters were used in this architecture to reduce toxicity and enable cleavability and biodegradability. [33][34][35] Similarly, polypyrrole nanoparticles were used for the pH-dependent release of piroxicam. [30,31] Also, the inner shell has been modified with free amine groups to coordinate copper ions and transport them across the BBB.…”
Section: Introductionmentioning
confidence: 99%
“…Similar to this approach, ionic interactions can be used to bind the pharmacophore to a nanoparticle. Examples are photosensitizer or cis‐platin‐loaded poly(methyl methacrylate) nanoparticles and antioxidants loaded into functionalized hPG . Similarly, polypyrrole nanoparticles were used for the pH‐dependent release of piroxicam .…”
Section: Introductionmentioning
confidence: 99%
“…8 We therefore selected polymethyl methacrylate nanoparticles (PMMA NPs) to enable the cellular uptake of our MB because of their high biocompatibility (they have previously been shown as highly biocompatible, even when used in vivo, because they are nontoxic and are excreted in feces at levels of up to 80 or 100% 9 ) and to avoid possible enzymatic degradation of the MB. 10,11 We used quaternary ammonium salts to functionalize the outer shells of the PMMA NPs, which provided a positively charged surface and thereby promoted the uptake of the negatively charged MB. We also labeled the core of the NPs with fluorescein (excitation wavelength 488nm, emission wavelength 525nm) to allow us to track their cellular uptake.…”
mentioning
confidence: 99%